25 million African Farming Families by 2025: Science-Development Partnerships for Scaling Climate-Smart Agriculture - Girvetz, Evan Hartunian; Rosenstock, Todd S.; Corner-Dolloff, Caitlin; Lamanna, Christine (2015)
The African Union-New Partnership for African Development (AU-NEPAD) has set a goal of 25 million farming families practicing Climate Smart Agriculture (CSA) by 2025 (Vision 25x25). This Vision 25x25 came out of the African Union Leaders “Malabo Declaration” of 2014 that set a path forward for African agricultural development over the next decade. Science and technical support is needed to help AU-NEPAD and its partners achieve this goal. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is developing a collaboration with AU-NEPAD to provide support to Vision 25x25. This poster describes some of the ways CCAFS is working to provide this support.